KONTRIBUSI SEKTOR PERTANIAN DALAM STRUKTUR EKONOMI DI KABUPATEN KAUR PROVINSI BENGKULU - Sari, Susi Roria (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
The purpose of the research is to analyze the agricultural subsector of the base as a role-maker and contribution in economic growth, to analyze the competitive advantage of agriculture sectorof Kaur Regency. The analysis methods used are Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share analysis (SS), and Overlay analysis. This study uses secondary data of constant price Regional Domestic Product of Kaur Regency in BengkuluProvince from 2011-2016. Result from the study finds, that agricultural sub-sectorwhich become the superior based on the result of overlay analysis between Location Quotient (LQ), Dynamic Location Quotient (DLQ) and the Shift-Share is subsector of food crop, plantation, agrecultural and fishery services, this means Subsector has excellence.